2016
DOI: 10.1163/22134808-00002493
|View full text |Cite
|
Sign up to set email alerts
|

Audio-Visual, Visuo-Tactile and Audio-Tactile Correspondences in Preschoolers

Abstract: Interest in crossmodal correspondences has recently seen a renaissance thanks to numerous studies in human adults. Yet, still very little is known about crossmodal correspondences in children, particularly in sensory pairings other than audition and vision. In the current study, we investigated whether 4–5-year-old children match auditory pitch to the spatial motion of visual objects (audio-visual condition). In addition, we investigated whether this correspondence extends to touch, i.e., whether children also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…In Experiment 1, one of the assumptions of the illusion was that higher pitches are usually associated with higher spatial positions, and lower pitches are associated with lower spatial positions. This metaphoric correspondence, which has been documented both adults 40,43 and children 41 , appears to facilitate both adult and children to at least subjectively report the finger length-illusion. Interestingly, Experiment 1 also revealed that the 'metaphoric' decreasing pitch is not sufficient to make participants perceive their finger to be shorter, and we took this as suggestion that experience with one's own body growing (and not shrinking) can constrain the perception of the illusion.…”
Section: Pointingmentioning
confidence: 64%
See 1 more Smart Citation
“…In Experiment 1, one of the assumptions of the illusion was that higher pitches are usually associated with higher spatial positions, and lower pitches are associated with lower spatial positions. This metaphoric correspondence, which has been documented both adults 40,43 and children 41 , appears to facilitate both adult and children to at least subjectively report the finger length-illusion. Interestingly, Experiment 1 also revealed that the 'metaphoric' decreasing pitch is not sufficient to make participants perceive their finger to be shorter, and we took this as suggestion that experience with one's own body growing (and not shrinking) can constrain the perception of the illusion.…”
Section: Pointingmentioning
confidence: 64%
“…Recent developmental studies have provided evidence that not only preschool children spontaneously match rising and falling sounds to visual objects moving along the same dimension (i.e., vertical, see 41 ), but even 3-month-old infants prefer 'metaphoric' correspondences between audio-visual compounds 42 . Thus, this predicts than even children may be sensitive to the auditory Pinocchio illusion, but to what extent audition may influence their body representation is the main objective of this study.…”
mentioning
confidence: 99%
“…Some previous research has examined cross-modal correspondences between visual motion and pitch. For instance, ascending and descending pitch modulations are linked to preferential looking towards upwards and downwards visual movement in children (Nava et al, 2016) and infants ; but see Lewkowicz and Minar, 2014 who did not observe a difference). However, this probably reflects spatial position rather than movement per se because the same tendency is found for static visual stimuli occupying high and low positions (Ben-Artzi and Marks, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Less is known about audio-haptic integration in children, except that developmental course would seem to be similar to audio-visual and visuo-haptic too (Nava et al, 2016). …”
Section: Development Of Multisensory Integrationmentioning
confidence: 99%